2022
DOI: 10.3390/nu14224865
|View full text |Cite
|
Sign up to set email alerts
|

A Year in the Life of U.S. Frontline Health Care Workers: Impact of COVID-19 on Weight Change, Physical Activity, Lifestyle Habits, and Psychological Factors

Abstract: Healthcare workers (HCWs) experienced significantly higher burdens and life demands due to the COVID-19 pandemic. This study sought to assess the longitudinal effects among HCWs throughout the pandemic. Qualtrics surveys collected self-reported data on weight changes, eating patterns, physical activity (PA), and psychological factors with data organized by timepoints prior to the pandemic (PP0—prior to March 2020), baseline (M0—January 2021), month 6 (M6—July 2021), and month 12 (M12—January 2022). Eating patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The COVID-19 Pandemic has been ongoing since 2020, with a significant negative impact on workers' health worldwide, not just limited to physical wellbeing, but also affecting psychological wellbeing (1)(2)(3)(4). COVID-19 has had an impact on occupational health both directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 Pandemic has been ongoing since 2020, with a significant negative impact on workers' health worldwide, not just limited to physical wellbeing, but also affecting psychological wellbeing (1)(2)(3)(4). COVID-19 has had an impact on occupational health both directly and indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Vancappel ( 39 ) reported that post-traumatic symptoms were also highly prevalent among French healthcare workers at the beginning of the COVID-19 crisis and they found a significant effect of the level of exposure to COVID-19 on affective symptoms. In the study by Oliver TL, the results implied that the COVID-19 pandemic had immediate effects on the eating patterns, weight changes, PA, and psychological factors of healthcare workers ( 40 ). In a large-scale survey during the COVID-19 pandemic, the results indicated that nurses who identified as women, working in ICUs, COVID-19 designated hospitals, and departments involved with treating COVID-19 patients had higher scores in mental health outcomes ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mental health impact of the COVID-19 pandemic on healthcare workers (HCWs) has been well documented in the literature ( 4 ). However, different from the very early stages of the pandemic ( 5 ), the phenomenon of overwork, burnout, and chronic mental health problems among HCWs has become a challenge that requires significant attention ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%